Tilawati Method Training in Learning Qur’anic Reading and Writing at Tadika Al Fikh Orchard, Malaysia - Isman Efendi Limbong; Alya Assyifa (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve teachers’ competence in teaching Qur’anic reading and writing through Tilawati method training at Tadika Al Fikh Orchard, Malaysia. The Tilawati method was selected because it offers a systematic, interactive, and practical learning approach suitable for early childhood education. The problems faced by the partner institution included teachers’ limited understanding of effective Qur’anic teaching methods and the lack of varied instructional techniques that could attract students’ interest. The program was implemented through observation, material presentation, demonstrations, direct practice, and evaluation stages. The results of the activity showed improvements in teachers’ understanding and skills in applying the Tilawati method in Qur’anic reading and writing instruction. In addition, teachers became more confident in creating active, enjoyable, and child-friendly learning environments. Through this training activity, it is expected that the quality of Qur’anic learning at Tadika Al Fikh Orchard Malaysia will continue to improve sustainably.